Predictive velocity control in a hilly terrain over a long look-ahead horizon. Issue 31 (2018) - Hamednia, Ahad; Murgovski, Nikolce; Fredriksson, Jonas
Abstract: This paper presents a computationally efficient velocity control of vehicles driving in a possibly hilly terrain and over long look-ahead horizons that may stretch to hundreds of kilometers. The controller decouples gear scheduling into an offline optimization problem, from the remaining optimization problem that governs two real-valued states. One of the states, the travel time, is adjoined to the objective by applying the necessary optimality conditions, which results into an online optimization problem that has kinetic energy as the single state. Finally an inner approximation is proposed for the online problem to obtain a quadratic program that can be solved efficiently. The efficiency of the proposed controller is shown for different horizon lengths.